If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 85 + 14 = 23 + y Combine like terms: 85 + 14 = 99 99 = 23 + y Solving 99 = 23 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 99 + -1y = 23 + y + -1y Combine like terms: y + -1y = 0 99 + -1y = 23 + 0 99 + -1y = 23 Add '-99' to each side of the equation. 99 + -99 + -1y = 23 + -99 Combine like terms: 99 + -99 = 0 0 + -1y = 23 + -99 -1y = 23 + -99 Combine like terms: 23 + -99 = -76 -1y = -76 Divide each side by '-1'. y = 76 Simplifying y = 76
| 4(2x-1)-6(3-x)=-8 | | 17x-34=17 | | 15x+21y=22 | | .5f-2=1.67f | | 2x^2=7x+17 | | 15x-21y=22 | | 3596=58a | | -3b+27=6 | | 67.5=a-24.2 | | 7.8=2m | | 3k=2(k+7) | | 2m^2+5m=2 | | x^2+60=2x+15 | | 17=x | | -5x+7y=10 | | 4(2-3x)+10(x-2)=7 | | -6g+12=12g+12 | | -7(6x+10)=-154 | | 90=2(x^2+60) | | x^6-5x^5-6x^4=0 | | 2x+x=4x | | 3-(12+2x)-6x=15-2x | | (3x+5)-7=0 | | 900000+111111= | | 4y=12-3x | | 2(-9+5x)=52 | | 2(-9+5x)=53 | | 2x-12-2x=4x-12 | | 1/32*12=s | | 3x^4-10x^3-24x^2-6x+5=0 | | 6u^2=-9u | | x-48.12=28.82 |